The Teacher and the Joy of Reading - Naik, J. V. (Journal of Information and Knowledge, 2014)
Reading for the intellectual growth is as important as eating for the physical growth of a human being. The advantages of reading are narrated with numerous examples from great personalities. How reading helps to increase the value of education and why reading is all the more important for teachers are discussed.